A hotel room on Mars: quarantine and the psychological view from the virtual front line. (December 2020) - Modini, Matthew; Vrklevski, Lil
Objective: Because of the COVID-19 pandemic, the implementation of quarantine for returning travellers and the effect this has on people's mental health has become a topical issue. This article briefly describes the historical context of quarantine, research around its impact on people's well-being, and the experiences of a clinical psychologist providing support to people in quarantine. Conclusions: Mental health professionals are in a unique position to assist people in quarantine, both in terms of counselling and ongoing research.